Kapasitas Negara dalam Penanganan Human Trafficking di Kamboja dan Implikasinya terhadap Human Security - Salfadillah Az Zahrah Sakaria (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
This study aims to analyze the Cambodian government's efforts to address human trafficking from a human security perspective. It employs a qualitative descriptive approach, utilizing secondary data from relevant journals, reports, and academic publications. The findings indicate that human trafficking in Cambodia has evolved into a hub for digital-based fraud linked to transnational cybercrime networks. Victims face not only labor exploitation but are also coerced into participating in online fraudulent activities, such as romance scams. This surge in human trafficking is driven by weak law enforcement, high levels of corruption, low public digital literacy, and the rapid expansion of the online gambling industry and special economic zones, which serve as operational bases for criminal activities. The Cambodian government has implemented various measures regarding prevention, protection, and law enforcement through regulations, international cooperation, victim rescue operations, and anti-fraud campaigns. However, the effectiveness of these policies remains limited due to the state's constrained capacity and the ability of criminal networks to continuously adapt to advancements in digital technology. The study concludes that addressing human trafficking in Cambodia requires strengthened governance, more intensive international cooperation, and improved public digital literacy.